Pengaruh Independensi, Kompetensi, Integritas, Objektivitas, dan Pengalaman Kerja Terhadap Kualitas Audit(Studi pada Kantor Akuntan Publik di Jawa Tengah) - Prasetyo, Danang Febri, Drs. Agus Endro Suwarno, Msi (2016)
This study aimed to analyze the influence of the independence, competence, integrity, objectivity, and work experience on audit quality. This study was conducted by distributing questionnaires to KAP in Central Java. Total sample is 46 respondents working in 5 KAP. This study is a quantitative study. Samples was determined using a convenience sampling. Hypothesis testing using multiple linear regression with SPSS version 20. All the variables in this study was measured by Likert Scale. The results of this study indicate that all independent variables have an effect on audit quality. The t-test showed the variables of independence, competence, integrity, objectivity, and work experience affect the quality of audit. The results obtained R2 values of 0.613 which means that 61.3% of variables that affect the quality of the audit could be explained by the variable independence, competence, integrity, objectivity, work experience, while the remaining 38.7% is explained by variabels outside the model.